Pemanfaatan Geographic Information System dalam Pemetaan Sekolah SMA Di Surabaya Barat - Rahmawati, Lailia; Pamungkas, Kris Maulana; Winarti, W (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The development of education in today's era has improved quite well, although there are still many who have not been able to keep up with the course of education that is being developed now. Technological development is also progressing rapidly. WebGIS is an important thing that is really needed in this digitalization era, it functions as information, especially in this discussion in the field of education. On current school information, the barrier is trying to eliminate the social gap in the form of a favorite school. This research was developed to make it easier for new students to graduate from junior high school to high school education and also make all schools equal without such a thing as a favorite school. with their address. This research uses the Web and Map which will be able to find out the distribution of schools according to the zoning area. The way this WebGIS works is that the user inputs the appropriate name and address into the web, then the system will provide information in the form of zoning for the closest school to the user's distance, which is expected that students will not choose the wrong school on the zoning path which allows low chances of entering the school.